(untitled) (Journal of actual problems of jurisprudence, 2024)
This article examines the experience of choosing the regime of exhaustion of trademark rights in conditions of import of goods to Kazakhstan. An attempt has been made to comprehend the limits of exclusive trademark rights in Kazakhstan. The author gives an overview of the currently used regime of exhaustion of rights in Kazakhstan, the application of this regime in the EAEU. The interests of consumers and business were considered in the context of existing legislation on intellectual property. The ways of using a trademark in Kazakhstan, the prohibition of such use by the trademark owner, as well as the limits of the trademark owner’s right to prohibit such use are analyzed. It is revealed that the exhaustion of trademark rights in Kazakhstan not only restricts the rights of the trademark owner, but also allows him to effectively build a licensing strategy, fight parallel imports, plan a brand protection policy, including against counterfeit products. The article used general scientific methods of cognition the method of synthesis and analysis, induction and deduction, as well as private scientific methods of cognition, such as historical and legal (studying specific situations), formal legal, comparative legal analysis and the method of interpretation of legal acts. The use of these methods made it possible to investigate the application of the trademark exhaustion regime, to understand the approaches of legal regulation in various countries on this issue, to study the peculiarities of the adoption of normative acts in Kazakhstan and their discrepancies, to analyze legal barriers preventing the effective application of the regional exhaustion regime in Kazakhstan, to study the results of attempts by Kazakh courts to apply the regional exhaustion regime in practice rights in various scenarios of consideration of cases, to identify the actual risks, caused by improper application of the exhaustion principle. Key words: trademark, exhaustion of trademark rights, parallel import, Kazakhstan, Eurasian Economic Union.